Papers in Boiotian Topography and History - Fossey, John M., (Classical Studies - Book Archive pre-2000., 1990)
To coincide with the publication of his large monograph 'Topography and Population of Ancient Boiotia', we are reprinting a series of 15 of Professor Fossey's previously published papers. These papers, scattered across many periodicals, were written during the preparation of the monograph; the latter, in its turn, makes frequent ref-erence to the papers. In this way, the two works complement each other; the papers also treat of detailed problems which could not have received the same full discussion in the monograph. The papers are divided into four sections: testimonia, Mykenaian Boiotia, Sites and History of Boiotia from Protohistoric to Classical Times, and Roman Boiotia.